Pelatihan Pembuatan Konten Pembelajaran Berbasis Video pada SMA Methodist 6 - Sinaga, Frans Mikael; Irviantina, Syanti; Pipin, Sio Jurnalis (Journal of Social Responsibility Projects by Higher Education Forum, 2024)
The use of information technology to support the teaching and learning process is considered important and necessary. It is not only the educators or teachers who are demanded to have the ability to use and utilize information technology, but students as well, in order to meet digital literacy competencies and be able to compete globally. At Swasta Methodist 6 High School, community service activities are carried out with the aim of improving students understanding in creating learning content using Canva and Wondershare Filmora tools. The availability of good facilities and infrastructure at school greatly assists students in utilizing technology to support the learning process. This activity was carried out for 2 days in the school's laboratory, and was attended by 43 students. The evaluation conducted with a pre-test and post-test showed an increase of 80% in the post-test for questions related to the use of Canva tools, and an increase of 60% in the post-test for questions related to the use of Wondershare Filmora tools.